(untitled) (Global Journal of Human-Social Science, 2018)
The effectiveness of a literary text is firstly determined by its language and how it succeeds in conveying the author’s message to his readers about the socio-cultural background of a given society in an imaginative way through the use of many narrative techniques. In fact, some writers tend even to employ different languages or varieties at both artistic and technical levels in order to provide realism. Thus, the main purpose of the current research paper is to explore language diversity and its effects on the literary text. In this regard, an investigation of Wasini Al Araj’s "The Disaster of the Seventh Night after the Thousand" was made, when a thorough examination was held with the help of some approaches in sociolinguistics and literature. To this end, the findings revealed that Al Araj succeeded in bringing different languages and varieties within the novel. Stated differently, it was found that the use of linguistic diversity provides both historical and social accuracy and realises realism through the introduction of myths and oral tales.